Rose oil inhalation protects against formaldehyde-induced testicular damage in rats - Köse, E; Sarsılmaz, M; Taş, U; Kavaklı, A; Türk, G; Dabak, Dö; Sapmaz, H; Ögetürk, M (My University, 2012)
In this experimental study, harmful effects of formaldehyde (FA) inhalation on sperm concentration, sperm quality, serum testosterone levels and the rat testes were investigated. In addition, the possible protective effects of rose oil against to these harmful effects were evaluated. For this purpose, 21 albino-Wistar rats were used. The rats in Group I were used as control group. When the rats of Group II were exposed FA (10 ppm/1 h) for 35 days, the rats of Group III inhalated rose oil (1 ml/1 h) after FA. The epididymal tissues were taken for sperm analysing and the testes were removed for histological examination. In addition, testosterone levels were determined from the blood samples. Although the testosterone levels, the epididymal sperm concentration, and the progressive sperm motility significantly decreased, the abnormal sperm rate significantly increased in the Group II when compared to Group I. In the Group III, these damages were seen less. When the rats in the Group II compared with the control group, there were serious histological damages. In the Group III, it was determined that the histological changes were less than group II. It can be expressed that serious damages occurred via formaldehyde exposure in male reproductive system and that the rose oil had protective effects against these damages.
Makale - Bilimsel Dergi Makalesi - Çok Yazarlı
Keywords: Formaldehyde Rat Rose oil Sperm Testes